2020
DOI: 10.1002/ps.5840
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Agaricus bitorquis mushroom as an strategy for the Integrated Pest Management of the myceliophagous mite Microdispus lambi

Abstract: BACKGROUNDThe phorid fly Megaselia halterata Winnertz (Diptera: Phoridae) is the principal vector of Microdispus lambi (Acari: Pygmephoroidea) in Spanish Agaricus bisporus Lange (Imbach) mushroom farms. This myceliophagous mite does not appear to be a pest in Agaricus bitorquis (Quél.) Sacc mushroom crops. This study explores the role of phorid flies as vectors of Microdispus lambi in Agaricus bitorquis mushroom crops.RESULTSThe incidence of M. lambi in A. bitorquis growing substrates did not reach appreciable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In European mushroom cultivation, biological agents such as entomopathogenic bacteria, nematodes and mites are used, and these strategies have low environmental impact and do not risk the development of resistance (Jess & Bingham, 2004; Jess & Kilpatrick, 2000; Jess & Schweizer, 2009; Navarro & Gea, 2014; Navarro et al., 2020). We previously reported two parasitoid wasps, Orthocentrus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In European mushroom cultivation, biological agents such as entomopathogenic bacteria, nematodes and mites are used, and these strategies have low environmental impact and do not risk the development of resistance (Jess & Bingham, 2004; Jess & Kilpatrick, 2000; Jess & Schweizer, 2009; Navarro & Gea, 2014; Navarro et al., 2020). We previously reported two parasitoid wasps, Orthocentrus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe and North America, the pests of the common mushroom, Agaricus bisporus (Lange) Sing., such as sciarids (Diptera: Sciaridae) and phorids (Diptera: Phoridae), are controlled by applying nematodes, microorganisms and predatory mites such as entomopathogenic nematodes of the genus Steinernema (Nematoda: Steinernematidae), S. feltiae (Filipjev) and S. carpocapsae (Weiser) (Erler et al., 2009; Jess & Bingham, 2004; Katumanyane et al., 2018; Navarro & Gea, 2014; Scheepmaker et al., 1998; Shamshad et al., 2008); the bacterium Bacillus thuringiensis (Berliner) var. israelensis (Shamshad, 2010); and predatory mites in the genus Hypoaspis (Acari: Hypoaspidae) (Jess & Bingham, 2004; Jess & Kilpatrick, 2000; Navarro et al., 2020). In these countries, integrated pest management (IPM) focusing on the use of natural enemies has been actively promoted, but this strategy has not been used much in Asian countries, including Japan.…”
Section: Introductionmentioning
confidence: 99%
“…of mushroom [20]. Other top mushroom cultivating states are California, Florida and Michigan [21]. India produces 2% of the world's whereas China contributes to 75%.…”
Section: Global Production Trend Of Mushroommentioning
confidence: 99%
“…farms [29,46,47] and on Agaricus bisporus (Lange) Imbach and Agaricus bitorquis (Quél.) Sacc crops [48]. White et al [49] reported cultivated A. bisporus to be more susceptible to phorid Megaselia halterata than wild species.…”
Section: Natural Distribution Of Phorid Fliesmentioning
confidence: 99%